Internet of things in disaster management: technologies and uses. (20th October 2021) - Bail, Rosangela de França; Kovaleski, João Luiz; da Silva, Vander Luiz; Pagani, Regina Negri; Chiroli, Daiane Maria de Genaro
ABSTRACT: In order to aid professionals in disaster management, efficient procedures and technologies are developed and adopted. This paper intends to present the results of a literature review on the use of the Internet of Things (IoT) in disaster management. Even though the IoT approach was defined many years ago, only recently its technologies have been enhanced and acquired greater clarity and scope. Internationally, scientific studies indexed in two databases, Scopus and Web of Science were found, selected and analyzed. Two portfolios of papers were generated: the first for the bibliometric analysis and, the second, leaner, for qualitative analysis retaining the contributions pertinent to the proposed theme. The literature review identified macro-discussions on the IoT in disaster management and applications of more specific devices or technologies. In disaster operations, the IoT is a target theme in the fields of Computer Science, Electronic Engineering and Environmental Engineering, especially useful in disaster mitigation, rescue, response, and recovery. The main positive impact is the facilitated communication between professionals, more robust data and monitoring of data for environmental management, first aid, people tracking, distribution of supplies and medicines, among other purposes.